THE INFLUENCE OF REVIEW CONTENT AND PRODUCT QUALITY ON PURCHASE INTEREST WITH TRUST AS AN INTERVENING VARIABLE - Arda, Mutia; Andriany, Dewi (Berajah Journal, 2024)
Today's technological advances have made many smartphone companies try to be at the forefront in order to attract buying interest from potential consumers. The aim of this research is to analyze the influence of review content and product quality on buying interest in Samsung series z smartphone products through trust in the buying interest of generation z consumers. The population in this study is all Medan city residents who use Samsung series z products. The sample in this study used a quota sampling of 100 people. The data collection technique in this research uses a questionnaire technique. The data analysis technique in this research uses a quantitative approach using statistical analysis using Auter Model Analysis, Inner Model Analysis and Hypothesis Testing. Data processing in this research uses the PLS (Partial Least Square) software program. The results of this research prove that directly review content, product quality and trust have a significant effect on buying interest, review content and product quality have a significant effect on trust and indirectly review content and product quality have a significant effect on buying interest through trust in the people of Medan city.